Composition design and crack resistance optimization method of red mud based foamed lightweight soil - Ning Zhang; Xingzhang Guo; Yuyan Li; Jian Zhang; Tingting Yu (Journal of ceramic processing research, 2024)
Utilizing industrial solid waste as a cementitious material for the production of foamed lightweight soil demonstrates significantpotential applications in the field of road engineering. In this paper, red mud based foamed lightweight soil was developed. And the crack resistance of red mud based foamed lightweight soil was evaluated. The findings indicate that the optimumcomposition for the red mud based cementitious material comprises 60 wt% red mud, 40 wt% slag, and 6 wt% NaOH. Thecompressive strength could reach 6.02 MPa and the initial setting time was 104 min at 28 d of curing. A composite foamingagent was formulated by selecting a combination of compound alkylamidopropyl betaine and xanthan gum. With a foam agentaddition of 5 wt%, the compressive strength of red mud based foamed lightweight soil reached 1.05 MPa at 28 d of curing, thefluidity reached 212 mm. Fiber can effectively inhibit the cracking of red mud based foamed lightweight soil, and 1.5 wt% glassfiber was determined to be the optimal dosage. The results can provide a certain basis for the application of red mud basedfoamed lightweight soil. KCI Citation Count: 0